2007
DOI: 10.1167/iovs.07-0264
|View full text |Cite
|
Sign up to set email alerts
|

Four Mutations (Three Novel, One Founder) inTACSTD2among Iranian GDLD Patients

Abstract: Although mutations in TACSTD2 among Iranian patients with GDLD were heterogeneous, E227K was found to be a common mutation. It is suggested that E227K may be a founder mutation in this population. Based on positions of known mutations in TACSTD2, significance of the thyroglobulin domain of the TACSTD2 protein in the pathogenesis of GDLD is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Early studies identified Trop-2 gene mutations to be associated with Gelatinous Drop-like Corneal Dystrophy (GDLD), a rare autosomal recessive genetic disease which leads to severe vision disorders and even blindness (14–16). More recently, studies have observed that Trop-2 is highly expressed in a number of human epithelial tumors compared with the restricted expression found in normal tissues, and that it is also associated with poor overall patient survival (35).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies identified Trop-2 gene mutations to be associated with Gelatinous Drop-like Corneal Dystrophy (GDLD), a rare autosomal recessive genetic disease which leads to severe vision disorders and even blindness (14–16). More recently, studies have observed that Trop-2 is highly expressed in a number of human epithelial tumors compared with the restricted expression found in normal tissues, and that it is also associated with poor overall patient survival (35).…”
Section: Discussionmentioning
confidence: 99%
“…The ancestry of the mutation in the Iranian pedigrees with respect to each other, and with respect to the same mutation in other populations could not be assessed because only limited regions of the genes were sequenced 33 . A founder mutation in TACSTD2 causing gelatinous drop‐like corneal dystrophy has been found in the Iranian population 34 . Observation of the c.371G>A mutation in the Iranian pedigrees further supports the proposal that perhaps only the mutation resulting in substitution of histidine for arginine at position 124 of TGFBIP results in the ACD phenotype 14 .…”
Section: Discussionmentioning
confidence: 99%
“…632delA p.Gln211ArgfsX60 632delA 22 c.653delA p.Asp218ValfsX53 c.653delA 25 c.679G>A p.Glu227Lys E227K 14 c.772_783delATCTATTACCTGinsT p.Lle258X 772 to 783del(ATCTATTACCTG) + 772insT 26 c.811delA p.Lys271SerfsX26 1117delA 13 …”
Section: The Ic3d Classification (C = Category)unclassified